A study on developing an effective and alternative harmless noisemaker and light display for young revelers, ages 20 years old and below for a fun and safe new year celebration in the Philippines - Abron, Lemuel D. (College of Fine Arts, University of the Philippines Diliman, 2017)
Filipinos are known for being revelers and their use of firecrackers and pyrotechnics has led to a lot of serious concerns and problems. While these noisemakers and light displays entertain people, its noise may also be as loud as the alarming news and cries that we hear every new year. The offered solutions and options in reducing the number of Firecracker's related injuries (FRI) are still ineffective and incomparable to the satisfactory experience that firecrackers provide; resulting to inconsistent changes in the FRI. With these issues in mind, a study to analyze it was conducted ti provide the most effective alternative harmless noisemaker and light display that could help in strengthening and promoting an incident-free and fun New Year celebration. Through this product, the users and non-users could still continue the tradition and the art of noisemaking and light displaying without sacrificing their safety and the environment's safety.